Trend of blood pressure control status in dialysis patients: a 10-year follow-up study - Yuko Ohta; Yuhei Kawano; Hiroshi Tsuruta; Hidetoshi Nakamura (Renal Replacement Therapy)
Abstract Background The management of blood pressure (BP) in dialysis patients is important because hypertension is a strong risk factor for cardiovascular disease. We investigated the changes in BP control status of hemodialysis patients over a 10-year period. Methods We analyzed the cases of 223 patients on hemodialysis at Kokura Daiichi Hospital in 2008. We determined the patients’ BP before and after dialysis, antihypertensive drugs, and clinical characteristics. The changes in BP control status were evaluated in 87 patients (52 males, 35 females, mean age 58 ± 12 years) who continued hemodialysis for 10 years. We also investigated the clinical characteristics of dropout patients during the follow-up period. Results Among the total 223 patients, 119 died during follow-up: 26 deaths had cardiovascular causes. Compared with the patients continuing hemodialysis, the dropout patients were significantly older and had significantly lower diastolic BP in 2008. In 2018 (the end of the 10-year follow-up), the patients’ diastolic BP values were significantly lower, while systolic BP values were unchanged compared with 2008. The number of antihypertensive drugs and the prescriptions of calcium antagonists and β-blockers were significantly increased. The achievement rate of good BP control (defined as < 140/90 mmHg) was not significantly different between 2008 and 2018; however, the frequency of intradialytic hypotension increased significantly. The group of patients with improved BP control at 10 years (n = 18) had a greater percentage of males, longer dialysis periods, and a lower frequency of intradialytic hypotension compared with the patients with persistently uncontrolled BP (n = 31). In addition, the frequency of intradialytic hypotension in the persistently controlled group at 10 years (n = 18) were lower compared with the worsened BP control group (n = 20). Conclusions The number of antihypertensive drugs used increased and the values of diastolic BP decreased over a 10-year period in hemodialysis patients, but patients’ BP control status did not change significantly. Intradialytic hypotension might be related to BP control status in hemodialysis patients.